Thrombocytopenia impairs host defense during murine Streptococcus pneumoniae pneumonia - van den Boogaard, Florry E; Schouten, Marcel; de Stoppelaar, Sacha F; Roelofs, Joris J T H; Brands, Xanthe; Schultz, Marcus J; van't Veer, Cornelis; van der Poll, Tom (Critical care medicine, 2015)
Streptococcus pneumoniae is the most common causative pathogen in community-acquired pneumonia. In patients, thrombocytopenia is correlated with an adverse outcome of pneumonia. Platelets can modulate the host response to infection in several ways, that is, by facilitating clot formation, production of antimicrobial proteins, and interaction with neutrophils. We studied the effect of thrombocytopenia during murine pneumococcal pneumonia. Animal study. University research laboratory. Mice. Pneumonia was induced by intranasal inoculation of S. pneumoniae. Platelets were depleted by anti-mouse thrombocyte serum; controls received nonimmunogenic serum. In separate studies, mice were treated with the platelet P2Y12 receptor inhibitor clopidogrel or placebo. Thrombocytopenic mice (platelet counts < 1% of uninfected controls) showed a reduced survival during pneumococcal pneumonia (27% vs 75% among controls; p = 0.003), which was associated with higher bacterial loads in lungs, spleen, and blood. Thrombocytopenic mice showed enhanced coagulation activation (thrombin-antithrombin complexes) in plasma. Proinflammatory cytokine levels were higher in plasma but not in lungs of thrombocytopenic mice. Although clopidogrel treatment strongly prolonged the bleeding time, it did not impact on bacterial loads during pneumococcal pneumonia. Platelets play a protective role during pneumococcal pneumonia independent of their aggregation.